Cause-effect relationship between air quality and public health in the city of Novi Sad based on the DPSEEA model - Kričković, Emina (Vojnotehnički glasnik / Military Technical Courier, 2021)
Introduction/purpose: The research subject in this article is the status of the air quality in the city of Novi Sad and its impact on the health of the population. Тhe relation between these two points will be presented using the DPSEEA model. The research aim of this article is to apply proper measures in order to mitigate negative effects on human health, based on scientific knowledge related to air quality influence on the health of the Novi Sad population. The basic hypothesis of this research implies that air quality affects Novi Sad’s population health. Methods: The following methods were used in this article: modeling, analysis-synthesis, statistic method, classification method, combining method, geographic-ecological method, method of geographic-medical description, method of the medical geography forecast as well as cartographic method. Results: Based on the DPSEEA model and the example of the air pollution in the city of Novi Sad, the following was identified: air pollution driving forces, pressures, state of the air quality, population exposure to air pollution, effects on human health as well as measures and actions that should be conducted. The mentioned model was also used to present the relationship between these segments. Conclusion: The given model deals with a wide spectrum of potential forces (harmful effects) and necessary community actions, bringing together professionals, people in the field and those from laboratories as well as managers in the area of environment and public health management, in order to tackle emerging problems in a comprehensive manner.